Know your neighbor : Charles A. Schempp (The Raton Daily Range Raton, New Mexico, 1964)
Newspaper Article on Charles A. Schempp and his many jobs he has held.
Master list item #:25
File location is in the Raton File Cabinet
Keywords: Schempp, Charles A; Garner, C.H.; Southwell, John; Errington, Joe; Farley, John; Leason, Jim; Schempp, Emma; Koehler, Fred; Cox, William; Gate City National Farm Loan Association; Southwell Mercantile company; Santa Fe Railroad; Baldwin-Buskirk Ranch; El Protal Hotel; Hotel Yucca; Seaburg Hotel; Local History; Biography; Life and Customs; Baseball; Pipelines; Railroad; Insurance; Ranching; Raton, New Mexico; Appleton City, St. Clair County, Missouri; Las Vegas, New Mexico; Central City, Colorado; Eadon, Colorado; El Paso, Texas